Which anomaly should I drill? Using spatial statistics to inform exploration in covered IOCG terranes. Issue 1 (1st December 2019) - Katona, Laszlo; Fabris, Adrian
Summary: This contribution presents a method for efficiently classifying geophysical anomalies and identifying regions and features that share characteristics of many known iron-oxide-copper-gold (IOCG) deposits of the Gawler Craton, and can therefore be used in drill target prioritization. Residual Bouguer gravity and reduced-to-pole total magnetic intensity grids over the Gawler Craton were transformed, generating polygon datasets representing populations of locally anomalous gravity and magnetic intensity. Taken as simple anomaly polygons, there are a very large number of features across the Gawler Craton (>39, 000 TMI and >10, 000 gravity). Superimposing mineral deposits over these features shows a clear spatial correlation between IOCG deposits and occurrences, and anomalies (>90% of deposits within 1, 000 m of an anomaly), but leaves thousands of anomalies of varying magnitudes that cannot all be related to IOCG mineralization. Eliminating TMI and gravity anomalies with a separation of more than 1, 000 m reduced the search space to ~20, 000 TMI features and ~8, 500 gravity features. Limiting the search to a statistically derived gravity threshold ≥0.4 mGal gravity anomalies, the exploration space is reduced to 798 gravity features with coincident TMI features within the Olympic Copper-Gold Province. The Anselin Local Morans I method was used to delineate geographic regions based upon spatial clustering of high magnitude anomalies. The spatial distribution and clustering characteristics of the gravity anomalies provide additional information and can be related to differing basement geology and deposit style. Terranes where lithologies and Cu-Au occurrences are commonly magnetite-rich show clustered high-magnitude gravity anomalies, and correlated spatially with the Mount Woods and Moonta domains within the eastern Gawler Craton. Importantly, it was found that the central, and currently most endowed, the Olympic Domain, was distinct in that it was dominated by spatial outliers (discrete high-magnitude density features). These results could be used as a starting point in developing IOCG exploration strategies, due to the high number of additional untested, spatially coincident gravity and magnetic anomalies that warrant further investigation.